Issues of independence in Northern Aboriginal‐state co‐management boards. (16th December 2018) - White, Graham
Abstract: A unique set of governance institutions has recently emerged in Canada's territorial North under finalized comprehensive land claims agreements: Aboriginal‐state co‐management boards for land‐use planning, environmental regulation and wildlife management. Public administration scholars have paid little attention to these boards and the issues – practical and theoretical – that arise with them. Board members are required to act "in the public interest" and not as representatives of the governments and Aboriginal organizations that nominated or appointed them. Yet the boards have strong co‐management mandates. This article examines this apparent contradiction as well as various issues of independence facing the boards: appointment processes and concerns relating to members' independence once appointed, board staffing and support, financial arrangements, and instances of government attempts to fundamentally alter boards or abolish them altogether.